Assessment of Potential Toxicological Risk for Public Health of Heavy Metals in Wheat Crop Irrigated with Wastewater: A Case Study in Sargodha, Pakistan - Iqbal Khan, Zafar; Ahmad, Kafeel; Ashraf, Muhammad; Aisha Akram, Nudrat; Rizwan, Yasir; Shaheen, Muneeba; Arshad, Fahim (Asian Journal of Chemistry, 2013)
In the present study, the concentrations of mineral elements in wheat (Triticum aestivum L.) plants was determined to observe the level of elemental pollution in Sargodha, Punjab, Pakistan as well as the abilities of the wheat plants to accumulate heavy metals from the soil supplied with sewage water. An experiment was conducted to study the transfer of heavy metals to the grains of wheat cv. Milate-2011 grown in soil without sewage-sludge treatment (control) and soil supplied with sewage-sludge. A number of heavy metals in soil and wheat grains were analyzed and results showed that Cr (5.63-6.21 mg/kg), Pb (5.54-7.08 mg/kg), Cu (12.25-13.64 mg/kg), Zn (31.85- 36.4 mg/kg), Mn (31.58-32.67 mg/kg) and Ni (3.43-4.32 mg/kg) were found in canal and sewage water irrigated wheat grains, respectively and were much higher than the toxic limit showing a severe risk of health. The Fe level (25.06-27.11 mg/kg) was below the toxic level, while Cd (0.02-0.03 mg/kg) level exceeded the maximum tolerable limit particularly for children i.e., 0.002-0.025 mg/kg. While soil Cr (24-36 mg/kg), Pb (80.21-94.84 mg/kg), Cu (23.4-28 mg/kg), Zn (65.2-72.8 mg/kg), Mn (62.8-73.2 mg/kg), Ni (23.4-25.5 mg/kg) and Fe (80.21-94.84 mg/kg) were found in canal and sewage water treated soil, respectively during this investigation and soil Cr, Cu, Ni and Zn levels were below the maximum permissible limits for soil, while the reverse was true for other metals. A significant correlation was found between the concentrations of metals in soil as well as their accumulation in grains except Fe concentration. The bio-concentration factor of these heavy metals was higher in wheat grains, so domestic sewage water may lead to heavy metal toxicity in humans if used unprocessed for irrigation purpose.